2019
DOI: 10.3389/fphar.2019.00594
|View full text |Cite
|
Sign up to set email alerts
|

Brevilin A Induces Cell Cycle Arrest and Apoptosis in Nasopharyngeal Carcinoma

Abstract: Nasopharyngeal carcinoma (NPC) is one of the most common malignant cancers in Southeast Asia and Southern China. Centipeda minima extract (CME) had previously demonstrated anti-cancer effects in human NPC. Brevilin A, a sesquiterpene lactone isolated from C. minima , has been reported to exhibit biological activities. In this study, we investigated its anti-NPC effect and further explored its molecular mechanisms. The effects of brevilin A were tested in the NPC ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…Brv-A induced G 2 /M phase arrest in MCF-7 cells in dose-dependent fashion which was consistent with previous published findings. 19 Sesquiterpene lactones are well-known compounds for inducing apoptotic cell death in various cancer cell types. 44 These compounds have also been confirmed to induce ROS generation.…”
Section: Discussionmentioning
confidence: 99%
“…Brv-A induced G 2 /M phase arrest in MCF-7 cells in dose-dependent fashion which was consistent with previous published findings. 19 Sesquiterpene lactones are well-known compounds for inducing apoptotic cell death in various cancer cell types. 44 These compounds have also been confirmed to induce ROS generation.…”
Section: Discussionmentioning
confidence: 99%
“…The whole plant has been employed as a TCM for millennia and is commonly treatment for indications such as rhinitis, sinusitis, cough, headache, swelling, and allergy (11). Phytochemical research has demonstrated CM mainly contain phenolic acids (e.g., isochlorogenic acid A and isochlorogenic acid C), flavonoids, and sesquiterpene lactones [e.g., Brevilin A, Arnicolide D; (12)(13)(14)(15)(16)]. Reports suggest that Centipeda minima extracts (CME) possess anti-inflammatory (17), anti-bacterial (18,19), and anti-allergic (20) effects.…”
Section: Introductionmentioning
confidence: 99%
“…Reports suggest that Centipeda minima extracts (CME) possess anti-inflammatory (17), anti-bacterial (18,19), and anti-allergic (20) effects. Previous studies have demonstrated the anti-cancer effects of CME, and compounds extracted from CM, in various cancers including nasopharyngeal carcinoma (13,14,21,22), leukemia (23), glioblastoma (24), lung cancer (25), and colon cancer (26), however, the effects of CME on breast cancer have to date, not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…et Aschers., and has been reported to exhibit anti-viral and anti-cancer effects, 5,6 in cancers such as colon carcinoma, glioblastoma and nasopharyngeal carcinoma. [7][8][9] However, the effects of BA on TNBC have not yet been demonstrated. Thus, in this study, we investigated the in vitro and in vivo anti-cancer effects of BA in TNBC.…”
Section: Introductionmentioning
confidence: 99%